Association between severe acute pancreatitis and new-onset diabetes: a propensity score-matched real-world study - Ba, Djibril M.; Hart, Phil A.; Qiu, Tian; Krishna, Somashekar G.; Gao, Xiang; Leslie, Douglas L.; Bradley, David; Maranki, Jennifer; Fofana, Kadiyatu; Chinchilli, Vernon M.; Pichardo-Lowden, Ariana R. (Frontiers in Endocrinology, 2025)
IntroductionAcute pancreatitis (AP) is an inflammatory disease of the exocrine pancreas characterized by tissue damage and sometimes necrosis. However, whether severe AP is associated with an increased risk of incident diabetes remains unclear based on real-world data. This study aims to examine the relationship between severe AP and new-onset diabetes after hospitalization.MethodsWe conducted a retrospective cohort study using the Merative™ MarketScan® claims database (2016–2023), identifying patients with AP and no prior history of diabetes at baseline. The exposure, severe AP, was defined by any of the following during hospitalization: pancreatic necrosis, hemodialysis, organ failure, or mechanical ventilation. We used multivariable stratified Cox proportional hazards regression models with propensity score strata to assess the association between severe AP and incident diabetes.ResultsThe matched study population consisted of 2,046 patients with severe AP and 2,046 patients with mild AP, with baseline characteristics well balanced between groups. Individuals with severe AP had a higher risk of developing diabetes compared with those with mild AP [adjusted hazard ratio (aHR) = 1.64, 95% confidence interval (CI): 1.30–2.06], after accounting for propensity score matching. The association between severe AP and incident diabetes was stronger in men (aHR = 2.03, 95% CI: 1.50–2.74) than in women (aHR = 1.06, 95% CI: 0.69–1.64; P-interaction = 0.02).DiscussionIn this large real-world data study, severe AP was associated with an increased risk of developing diabetes. These findings underscore the importance for glycemic surveillance and the need to consider proactive management of severe AP patients to mitigate their risk of poor health outcomes.